P2Y6 Receptors Regulate CXCL10 Expression and Secretion in Mouse Intestinal Epithelial Cells - Salem, Mabrouka; Tremblay, Alain; Pelletier, Julie; Robaye, Bernard; Sévigny, Jean (Frontiers in Pharmacology, 2018)
In this study we investigated the role of extracellular nucleotides in chemokine (KC, MIP-2, MCP-1 & CXCL10) expression and secretion by murine primary intestinal epithelial cells (IEC) with a focus on P2Y6 receptors. QRT-PCR experiments showed that P2Y6 was the dominant nucleotide receptor expressed in mouse IEC. In addition, the P2Y6 ligand UDP induced expression and secretion of CXCL10. For the other studies, we took advantage of mice deficient in P2Y6 (P2ry6-/-). Similar expression levels of P2Y1, P2Y2, P2X2, P2X4 and A2A were detected in P2ry6-/- and WT IEC. Agonists of TLR3 (poly(I:C)), TLR4 (LPS), P2Y1 and P2Y2 increased the expression and secretion of CXCL10 more prominently in P2ry6-/- IEC than in WT IEC. CXCL10 expression and secretion induced by poly(I:C) in both P2ry6-/- and WT IEC were inhibited by general P2 antagonists (suramin, RB-2), by apyrase and by specific antagonists of P2Y1, P2Y2, P2Y6 (only in WT) and P2X4. Neither adenosine nor an A2A antagonist had an effect on CXCL10 expression and secretion. Macrophage chemotaxis was induced by the supernatant of poly(I:C)-treated IEC which was consistent with the level of CXCL10 secreted. Finally, the non-nucleotide agonist FGF2 induced MMP9 mRNA expression also at a higher level in P2ry6-/- IEC than in WT IEC. In conclusion, extracellular nucleotides regulate CXCL10 expression and secretion by IEC. In absence of P2Y6, these effects are modulated by other P2 receptors also present on IEC. These data suggest that the presence of P2Y6 regulates chemokine secretion and may also regulate IEC homeostasis.